Terapi Akupresur Pada Payudara Titik Meridian Terhadap Produksi ASI Post Sectio Caesarea - Asrawaty Agussalim; Arie Maineny; Asri Widyayanti; Hasnawati Hasnawati; Novi Dwi Astuti (Program Studi D III Kebidanan Akademi Kesehatan Sapta Bakti Bengkulu, 2026)
Caesarean section delivery causes problems with breastfeeding barriers in early life. The coverage of exclusive breastfeeding for infants aged <6 months was 24.8% in the study area, lower than the national coverage of 33.2% and Central Sulawesi Province of 32.2%. Acupressure therapy stimulates breast muscles, improves blood circulation, induces the release of oxytocin, endorphin and prolactin hormones. The purpose of this study was to determine the effect of acupressure therapy on the breast area on breast milk production after Caesarean section. The quasi-experimental research design used a pretest-posttest one group design approach. The probability sampling technique was consecutive sampling with a sample size of 22. The independent variable was acupressure therapy on the breast area, the dependent variable was breast milk production after Caesarean section. The intervention was carried out for 2 days every morning and evening, with acupressure frequency of 4 times, and the duration of therapy for each session was 10–15 minutes. Data collection used an observation sheet. Data processing used the SPSS version 20 application, data analysis was the Parametric Paired Sample T-Test with a significance value of p value <0.05. Breast milk production before acupressure was 8.95 ml, and after acupressure was 22.82 ml. There is an effect of acupressure on post-CS on increasing breast milk production with a p value of 0.000<0.05. There is an increase in breast milk production in Post-Cesarean Section mothers after acupressure techniques are performed on the meridian points.